Magnetic ethylene-based periodic mesoporous organosilica supported palladium: An efficient and recoverable nanocatalyst for Suzuki reaction - Neysi, Maryam; Elhamifar, Dawood (Frontiers in Chemistry, 2023)
In the present study, a novel magnetic ethylene-based periodic mesoporous organosilica supported Pd-Schiff base complex (Fe3O4@PMO/SB-Pd) was prepared, characterized and applied as a recoverable nanocatalyst for green synthesis of Suzuki products. Chemical composition, magnetic and thermal behavior, morphology and particle size of Fe3O4@PMO/SB-Pd were investigated by using FT-IR, TGA, EDX, VSM, PXRD, TEM and SEM analyses. The Fe3O4@PMO/SB-Pd nanocomposite was applied as an efficient nanocatalyst in the Suzuki reaction under ultrasonic conditions giving corresponding products in high yield. Some advantages of this study are simple purification of products, the use of water solvent, easy catalyst separation, short reaction time and high catalyst efficiency and recoverability.